Quality of Services Publishing Record of Fisheries (BPKP) in The Marine and Fisheries Office South Sumatera Province - Israk, Galamda; Widodo, Slamet; Alfatih, Andy (HM Publisher, 2018)
ABSTRACT This study aims to determine the quality of service issuance of Proof of Registration of Fishing Vessels (BPKP) in the Department of Maritime Affairs and Fisheries of South Sumatra Province and what factors influence it. Data collection techniques used were the distribution of questionnaires to 60 respondents who were capture fisheries business actors with a Likert Scale assessment, as well as conducting unstructured interviews, non-participant observation and secondary data collection. The dimensions used are tangible, reliability, responsiveness, assurance and empathy. The value of service quality based on tangible dimensions is 4.2 or good, based on the reliability dimension is 4.1 or good, the responsiveness dimension is 4.0 or good, the guarantee dimension is 4.1 or good, and based on the empathy dimension is 4.1 or good. Of all these parameters, it was concluded that the quality of BPKP issuance services in the Department of Maritime Affairs and Fisheries of South Sumatra Province in 2016 was good with a score of 4.1. The conclusion is based on an assessment of an average of 58 respondents or 97.4% of respondents.